Integrated Smart Agricultural Field Protection and Automatic Irrigation System (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
This paper presents an integrated smart agricultural field protection and automatic irrigation system using advanced Internet of Things (IoT) technology. The proposed system is designed to monitor environmental conditions such as soil moisture, temperature, and humidity in real-time. The collected data is processed using a NodeMCU microcontroller and transmitted to a Raspberry Pi for intelligent decision-making. Based on soil moisture levels, the system automatically controls irrigation using a relay-driven water pump, thereby reducing water wastage and improving efficiency. In addition to irrigation, the system incorporates a field protection mechanism using an ESP32 camera module, which continuously monitors the agricultural field for any intrusion or unwanted activities. A GSM module is integrated to send real-time alerts to farmers, ensuring quick response and improved crop safety. Furthermore, the system includes an intelligent animal detection mechanism. When an animal enters the field, the system analyses the type of animal and generates a specific irritating sound to repel it. To prevent animals from getting habituated to a particular sound, the system is programmed to automatically change the sound at regular intervals. For each type of animal, multiple irritating sounds are stored, and the system cycles through these sounds every five days. This dynamic sound variation ensures continuous effectiveness of the deterrent mechanism and enhances field protection. The proposed system minimizes manual labor, optimizes water usage, and improves overall agricultural productivity. It is cost-effective, reliable, and suitable for modern smart farming applications
Keywords: Smart Agriculture; IoT; Automatic Irrigation System; Field Protection; Animal Detection; ESP32 Camera; Raspberry Pi; Soil Moisture Sensor; GSM Module; Sound Deterrent System; Dynamic Sound Variation